AVAILABILITY OF LANGUAGE INPUT, CONDUCIVE ENVIRONMENT IN LEARNING LANGUAGE AND MOTIVATION AND ITS RELATION TO LANGUAGE ACQUISITION - Daristya Lyan Rian Dalu; Heny Setyawati; Muhammad Affandi Arianto; Nurul Azizaturrohmah (LET: Linguistics, Literature and English Teaching Journal, 2016)
There are several factors affecting learners’ language proficiency. Those are availability of language input, conducive social environment, availability authentic materials, and motivation. This case study aims to investigate the way how the learner’s language proficiency in speaking English is, how the availability of language input affects the learner’s language acquisition, what the roles of the environmental factors in helping the learner mastering English are, and how the learner motivates himself in learning English. In-depth interview is used to collect the data and the subject of this study was the eleventh grade student from a science class at SMAN 3 Malang. The results show that he answered all of the questions briefly and clearly as if he got all of the ideas from each of the question. In terms of his fluency, it is in scale 4 because he spoke with near-native fluency and any hesitation did not interfere the communication. Besides, his pronunciation and intonation is in scale 3. It was concluded that there were only few mistakes in his pronunciation although he used Indonesian accent. In using grammar and vocabulary, the subject of this study is in scale 3 because he mostly used grammar and vocabulary choice or diction correctly. The subject shows that he does intentional learning. He takes English course instead of just learn English at school. Besides, the kinds of motivation found are integrated and instrumental motivation.